At the core of cyberaggression: A group‐based explanation. Issue 1 (25th October 2021) - Trifiletti, Elena; Giannini, Marco; Vezzali, Loris; Shamloo, Soraya E.; Faccini, Martina; Cocco, Veronica M.
Abstract: In this study, prototypicality of the aggressor was tested as a group‐level factor predicting social media users' active participation in cyberaggression. Participants were exposed to a fictitious conversation, in which either a prototypical versus non‐prototypical user posted an aggressive comment as a reply to a provocative comment. In line with self‐categorization theory, we hypothesized that bystander participants would post an aggressive comment and rate the aggression as acceptable to a greater extent in the prototypical than in the non‐prototypical condition. Furthermore, we predicted that perceived normativity of aggression would mediate the effect of prototypicality. Results supported these predictions and showed that prototypical members affect the extent to which collective aggressive behaviors in online interactions are approved and enacted. These findings highlight the importance of group‐level factors in the study of cyberaggression and provide important information for understanding the psychological underpinnings of collective forms of online aggression.